PENINGKATAN KUALITAS PEMBELAJARAN SEJARAH AGRARIA MELALUI PENERAPAN MODEL GROUP INVESTIGATION DALAM PROSES BELAJAR-MENGAJAR - Musadad, Akhmad Arif (Jurnal Inovasi Pendidikan, 2011)
The purpose of research is to increase the agrarian affairs history learning process quality through the group investigation model application within study and learning process in history education FKIP UNS. The research is accomplished with the method of classroom action research. It contains the actions that aimed to improve the quality a system and the practical within that system, In this research, the system is study and agrarian affairs history study and learning process that accomplished at semester IV in study program of history education P.IPS FKIP - UNS that addressed in J1. Ir. Sutami number 36 A Surakarta. The subject of research is the history education study program students who join agrarian affairs history subject. Meanwhile, the object is the activity of study and learning process that consists: activity of learning by the lecturer, activity of student's study and the learning atmosphere. The research is implemented with participative collaborative approach among the support lecturer (the chairman of research), associate lecturer (the member of research), and students so that will be sharing in each activity phase. This research has the reflective character, that intend to improve rational stability of the actions that done. The research is implemented with the process of in stages research. It consists of four activity phases that are action plan, implementation, and reflection. This research is implemented within two cycles. Cycle I is as an action implementation, and cycle I1 is as betterment. Appropriate with the purposes, the low of learning process quality becomes the problem of this research. This matter signed by the low of ability to make learning process implementation plan, learning process procedure and the students study activity. To increase the learning process quality, the researcher did many actions that are: investment the right concept about the effectiveness of history learning process, training of learning process implementation plan arrangement, and peer teaching that intend to increase the lecturer ability within implement the learning process procedure. It related with group investigation model implementation. After the actions accomplished, and the result can be implemented in study and learning process. It approved from a cycle to the next cycle. Then the quality of learning process is more and more. This matter reflected from: the increase of ability within arrange the learning process implementation plan, and the ability in implement the learning process procedure. The increase of learning process quality impact to the increase the students study activity and the betterment of learning process atmosphere.